Pengaruh Work Life Balance, Lingkungan Kerja dan Kompensasi terhadap Loyalitas Perawat pada Rumah Sakit Umum BKM Painan - Anggraini, Sintia; Anwar, Saiful (Lembaga Yasin AlSys, 2026)
Nurse loyalty is an important concern in hospital human resource management because it is related to workforce stability and the quality of health services. However, research specifically discussing the effects of work-life balance, work environment, and compensation on nurse loyalty at BKM Painan General Hospital remains limited. This study aims to analyze the effects of work-life balance, work environment, and compensation on nurse loyalty. This study used a quantitative approach with a survey design, involving 90 nurses selected through total sampling. Data were collected using a questionnaire and analyzed through multiple linear regression with the assistance of SPSS 25. The results show that work-life balance has no significant effect on nurse loyalty, the work environment has a positive and significant effect on nurse loyalty, while compensation has no significant effect on nurse loyalty. This finding contributes to the development of the human resource management literature, particularly regarding factors that influence the loyalty of health workers. The conclusion of this study emphasizes that a safe, comfortable, and conducive work environment is an important factor in increasing nurse loyalty at BKM Painan General Hospital. The practical implications of this study indicate the need to strengthen the quality of the work environment as a hospital human resource management strategy to support nursing workforce stability and improve the quality of health services.